1994
DOI: 10.1515/bchm3.1994.375.8.521
|View full text |Cite
|
Sign up to set email alerts
|

In vivoBinding of Human Inter-α-Trypsin Inhibitor Free Heavy Chains to Hyaluronic Acid

Abstract: In vivo binding of human inter-alpha-trypsin inhibitor to hyaluronate was investigated by immunoelectrophoretic techniques. Pathological synovial fluids and follicular fluids both contain high concentrations of soluble hyaluronate. Heavy chain epitopes of inter-alpha-trypsin inhibitor were firmly associated with the hyaluronate in synovial fluid and follicular fluid. The hyaluronate-bound inter-alpha-trypsin inhibitor epitopes did not cross-react immunologically with bikunin. Several hyaluronate-bound inter-al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
36
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 21 publications
(10 reference statements)
3
36
0
Order By: Relevance
“…6). An early study also found the retention of SHAP-HA complex when synovial fluids or follicle fluids were subjected to agarose gel electrophoresis (27). Our results were in agreement with the observation and further indicated that the SHAP-HA complex itself was enough to form the aggregates, which implies an interesting role for SHAP in the regulation of HA aggregation.…”
Section: Discussionsupporting
confidence: 90%
“…6). An early study also found the retention of SHAP-HA complex when synovial fluids or follicle fluids were subjected to agarose gel electrophoresis (27). Our results were in agreement with the observation and further indicated that the SHAP-HA complex itself was enough to form the aggregates, which implies an interesting role for SHAP in the regulation of HA aggregation.…”
Section: Discussionsupporting
confidence: 90%
“…9,10) After the binding of the ITI family to hyaluronic acid, bikunin is released by an unknown mechanism and the heavy chains bind to hyaluronic acid covalently. [18][19][20] A feature of IHRP is its sensitivity to plasma kallikrein like kininogens.…”
Section: Quantitation Of Ihrp In Human Plasmamentioning
confidence: 99%
“…Thus hyaluronan isolated from the synovial fluid of patients with rheumatoid arthritis has been found to contain covalently linked heavy chains (19,20). Furthermore, upon inflammation, fibroblasts and monocytes secrete a protein named TSG-6, which reacts with I␣I by displacing H1 and forming a covalent link with the chondroitin sulfate of bikunin (21).…”
Section: Inter-␣-inhibitor (I␣i)mentioning
confidence: 99%